Dielectric properties of Y and Nb co-doped TiO2 ceramics - Xianwei Wang (Nature Portfolio, 2017)
Abstract In this work, the (Y0.5Nb0.5)xTi1−xO2 (x = 0.001, 0.01, 0.02, 0.04, 0.06 and 0.1) ceramics (as called YNTO) were fabricated by synthesized through a standard solid-state reaction. As revealed by the X-ray diffraction (XRD) spectra, the YNTOs exhibit tetragonal rutile structure. Meanwhile, the grain size of YNTO ceramics increased and then decreased with the increase of x value, and the largest value reached when x = 0.02. All the YNTO samples display colossal permittivity (~102–105) over a wide temperature and frequency range. Moreover, the optimal ceramic, (Y0.5Nb0.5)0.02Ti0.98O2, exhibits high performance over a broad temperature range from 20 °C to 180 °C; specifically, at 1 kHz, the dielectric constant and dielectric loss are 6.55 × 104 and 0.22 at room temperature, and they are 1.03 × 105 and 0.11 at 180 °C, respectively.